The role of a newly isolated strain Corynebacterium pollutisoli SPH6 in waste activated sludge alkaline fermentation. (February 2020) - Pang, Lina; He, Ye; Liu, Xuna; Li, Junjie; Yang, Ping
Abstract: Alkaline fermentation has been considered as one of the efficient methods for waste activated sludge (WAS) treatment, but usually limited by microbial fermentation activities under extreme pH condition. One newly isolated alkali-tolerant strain Corynebacterium pollutisoli SPH6 was used to assess its potential role and effect on WAS alkaline fermentation process. Results from response surface method showed that the optimal organic nitrogen degradation rate by SPH6 was obtained under temperature of 35 °C, initial pH of 10, shaking speed of 80 rpm, inoculation ratio of 6.5%. Batch-scale experiments demonstrated that, compared with the control group, the inoculation of SPH6 finally achieved higher productions with 13.4% of carbohydrates, 27.1% of protein and 25.4% of total volatile fatty acids (VFAs), and more predominant functional bacteria characterized by high-throughput sequencing, such as genera Acinetobacter in phylum Proteobacteria, Tissierella and Acetoanaerobium in phylum Firmicutes . The strain SPH6 might play a vital role in maintaining and facilitating the growth and diversity of functional bacteria in WAS alkaline fermentation process. It has implied promising practical application of the present strain in enhancing WAS reduction and utilization. Highlights: A novel alkali-tolerant strain Corynebacterium pollutisoli SPH6 was isolated. The strain SPH6 improved the VFAs accumulation in WAS alkaline fermentation. The strain SPH6 facilitated functional bacterial community to be dominant.